2021
DOI: 10.1007/s00158-021-03009-8
|View full text |Cite
|
Sign up to set email alerts
|

LayOpt: an educational web-app for truss layout optimization

Abstract: A new interactive truss layout optimization web-app has been developed for educational use. This has been designed to be used on a range of devices, from mobile phones to desktop PCs. Truss designs are first generated via numerical layout optimization and then rationalized via geometry optimization. It is then shown that these designs can be simplified using a computationally inexpensive process that allows the user to control the trade-off between complexity and structural volume. The process involves the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Next, the orthotic blank is thickened and transformed into a Boundary Representation object via a feature-based reconstruction (Mayer et al, 2022). This serves as an input parameter for a design space, which is volume optimized in the next step (Fairclough et al, 2021). The applied loads and constraint locations (Taha et al, 2016;Wong et al, 2016;Mitternacht and Lampe, 2006) of the orthosis…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the orthotic blank is thickened and transformed into a Boundary Representation object via a feature-based reconstruction (Mayer et al, 2022). This serves as an input parameter for a design space, which is volume optimized in the next step (Fairclough et al, 2021). The applied loads and constraint locations (Taha et al, 2016;Wong et al, 2016;Mitternacht and Lampe, 2006) of the orthosis…”
Section: Methodsmentioning
confidence: 99%
“…However, as these filter functions are not necessary for the understanding how the optimization works, they will not be discussed further here. The complete implementation follows exactly Fairclough et al (2021) and can be found there. Finally, a solution with a minimum number of beams is obtained, which just withstands the loads.…”
Section: Iced23mentioning
confidence: 99%
“…• Stage 2 (improving practicality): Various tools can be utilized to improve the practicality of the designs. In addition to the rationalization techniques described in Section 2.4.1, the automatic simplification method described in [22,46] can be used to e.g. control the number of members, connections and/or the complexity of connections.…”
Section: Implementation: Rhino-grasshopper Plug-inmentioning
confidence: 99%
“…Although it is possible to derive truss layouts from topology optimization solutions (e.g. [13][14][15]), numerical layout optimization employing a 'ground structure' provides a powerful and highly efficient alternative for such structures, being capable of rapidly identifying (near-) optimal structural forms (e.g., [16][17][18][19][20][21][22]). For example with truss layout optimization, an optimal structure formed from discrete truss elements is sought, and linear programming (LP) can be used to solve basic problems.…”
Section: Introductionmentioning
confidence: 99%
“…The DLO has been subsequently applied to masonry wall [ 34 ], to retaining walls [ 35 ], in geotechnics [ 36 ], and to the yield-line method for slabs [ 37 ], and several examples of application to different civil engineering problems can be found in [ 38 ]. The computational efficiency of a discrete approach to layout optimization is shown in some recent papers [ 39 , 40 ]. Moreover, the DLO has been applied to steel connections [ 41 ] and used to calculate foundation over volcanic rock with a low density [ 42 ].…”
Section: Introductionmentioning
confidence: 99%